CYBERSECURITY AND PUBLIC TRUST IN DIGITAL GOVERNANCE: FOCUSING ON CITIZEN TRUST - Preecha, Jidapa (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to investigate the critical role of cybersecurity in fostering public trust toward digital government services. Method: A survey was conducted involving 30 citizens to analyze their perceptions and trust levels in e-governance systems amidst increasing cyber threats. Results: Findings reveal that 86% of respondents who have engaged with government digital services express a lack of trust, primarily due to concerns over cyber disruptions and fraud. These vulnerabilities undermine the perceived security and reliability of digital governance platforms. Novelty: This research highlights the direct correlation between cybersecurity challenges and public trust in digital government services, emphasizing the urgent need for robust cybersecurity frameworks to safeguard personal data. By focusing on citizen attitudes, this study contributes empirical evidence that informs policymakers and practitioners about the social implications of cybersecurity weaknesses in e-governance, thereby guiding the development of more secure and trustworthy digital public service infrastructures.